DESCRIPTION OF PARENTING PATTERNS IN PRESCHOOL CHILDREN AT DHARMA WANITA PERSATUAN MEDALEM KINDERGARTEN - Astria Putri Wahyu Sutrisno; Siti Maimuna (Prodi keperawatan sidoarjo, politeknik kesehatan kemenkes surabaya indonesia, 2023)
Preschool-age children are those aged between 3 to 6 years, in this period physical growth slows down and psychosocial and cognitive development increases. Proper parenting by parents is the basis of child development that will make them a person of good character for themselves and their environment. Parents must choose parenting patterns that suit their children's needs. This study aims to identify the types of parenting patterns of parents in preschool children at the Dharma Wanita Persatuan Medalem Kindergarten, Tulangan Sub-district, Sidoarjo District. This research method uses descriptive research. Using total sampling with a total of 43 respondents with univariate analysis techniques by presenting frequency distribution tables. The results showed that most of the parents of preschool children in the Dharma Wanita Persatuan Medalem Kindergarten, Tulangan Subdistrict, Sidoarjo District were included in the early adult age category (60%), most of the parents' final education was high school (74%), and most of them were working parents (60%). All parents (100%) applied democratic parenting, 10 (23%) applied permissive parenting and 21 (49%) parents also applied authoritarian parenting. Parents do not only apply one type of parenting but one or more parenting patterns. Parenting must be applied according to the age, needs and abilities of the child. Keywords: Parenting Style, Preschool Children, Development